Knowledge and skills in combating stunting in toddlers in Aceh Besar regency (a comparative study of BKKBN cadres with Integrated Service Post cadres) - Majid, Abdul; Hermansyah, Hermansyah; Zahara, Meutia; Abdullah, Asnawi; Hafnidar, Hafnidar (Science Midwifery, 2024)
Stunting is a critical issue with irreversible consequences on children's growth and development. In Ingin Jaya and Indrapuri districts, stunting is a significant concern. This research examined the knowledge and skills of TPK and Posyandu cadres in tackling stunting in Aceh Besar Regency. The study included 50 TPK cadres and 50 Integrated Service Post cadres actively engaged in Want Jaya and Indrapuri districts in 2022. Analysis revealed no significant differences in knowledge (P=0.562) and skills (P=0.445) between the cadres. Cadres' motivation level emerged as the most influential factor impacting stunting prevalence, with lower motivation associated with a 4.67% increase in stunting village score (P=0.030). These findings offer valuable insights for addressing stunting and inform effective management strategies in rural areas. While no significant differences were found in knowledge, skills, education, and occupation between TPK and Integrated Service Post cadres in Aceh Besar District, variations were observed in the distance from the village to the district capital. Inadequate knowledge and motivation in both cadre groups significantly affect efforts to combat toddler stunting.